Revitalizing Adab Education in Pesantren as a Strategy for Strengthening the Morals of the Younger Generation - Firmansyah Firmansyah; Gatot Kaca; Miftahul Husni; Emma Himayaturohmah; Mukti Ali (PT. Pusmedia Group Indonesia, 2025)
Pesantren as an Islamic educational institution has a strategic role in shaping the character and morals of the younger generation. Globalization, technological advances, and shifting social values demand an updated moral development system that is relevant to the current context. This study aims to describe and analyze the revitalization strategy of adab education in pesantren and examine its effectiveness in strengthening the morals of the younger generation. The research used a descriptive qualitative approach with case studies in 3 (three) pesantren representing traditional, modern, and hybrid models. Data were collected through in-depth interviews with kyai, ustaz, and santri; observation of learning activities and adab coaching; and review of curriculum documents. Data analysis was done thematically to identify effective revitalization patterns. The results showed that the revitalization strategy of adab education in pesantren includes reconstructing the curriculum based on Qur'anic and hadith values, strengthening the exemplary (uswah hasanah) of educators, and using adaptive learning methods that combine pesantren traditions with modern educational technology. The implementation of this strategy is proven to increase moral awareness, discipline, social attitudes, and the resilience of santri to negative environmental influences. This study concludes that the revitalization of adab education is an effective strategy for strengthening the morals of the younger generation, and recommends the development of a sustainable adab education model that is responsive to the challenges of the times.